Adherence to gout management recommendations of Chinese patients. Issue 45 (November 2017) - Sheng, Feng; Fang, Weigang; Zhang, Bingqing; Sha, Yue; Zeng, Xuejun
Abstract : Abstract: Though efficacious and affordable treatments for gout are widely available, gout is still not well controlled in many countries of the world including China. To investigate patient adherence to gout management recommendations and potential barriers in Chinese male gout patients, a survey was carried out by telephone interview in male patients registered in the gout clinic at Peking Union Medical College Hospital. Adherence to dietary and medication recommendations was measured by a food frequency questionnaire and proportion of cumulative time adherent to chemical urate-lowering therapy (ULT), respectively. Dietary adherence was defined as consumption of alcohol, seafood and animal organs less than once per month, and reduced red meat after dietary counseling. Medication adherence was defined as ULT ≥80% of time in the past 12 months for patients with indications. Logistic regression models were used to identify patient characteristics associated with management adherence. Reasons for nonadherence were also sought by open-end questions. Dietary and medication adherence were 44.2% and 21.9%, respectively. Older age (odds ratio [OR] 7.90, 95% confidence interval [CI] 2.49–25.04 for age ≥60), higher serum uric acid (sUA) levels (OR 3.53, 95% CI 1.42–8.75 for the highest quartile), and tophi (OR 2.31, 95% CI 1.12–4.77) were associated with dietary adherence independently, while tophi (OR 14.05, 95% CI 2.67–74.08) and chronic kidney disease (OR 16.66, 95% CI 2.63–105.37) were associated with medication adherence independently. Reasons that patients reported for nonadherence to medication included remission after treatment (35.3%), concerns for potential side effects (22.7%), insufficient patient education (8.7%), and adverse events (8.2%). Patient adherence to gout management recommendations is poor in China. Older age, increased disease burden, and specific comorbidities were associated with management adherence.